Plants response to light stress - Shi, Yafei; Ke, Xiangsheng; Yang, Xiaoxia; Liu, Yuhan; Hou, Xin (Journal of genetics and genomics, 2022)
Plants require solar energy to grow through oxygenic photosynthesis; however, when light intensity exceeds the optimal range for photosynthesis, it causes abiotic stress and physiological damage in plants. In response to high light stress, plants initiate a series of signal transduction from chloroplasts to whole cells and from locally stressed tissues to the rest of the plant body. These signals trigger a variety of physiological and biochemical reactions intended to mitigate the deleterious effects of high light intensity, such as photodamage and photoinhibition. Light stress protection mechanisms include chloroplastic Reactive oxygen species (ROS) scavenging, chloroplast and stomatal movement, and anthocyanin production. Photosynthetic apparatuses, being the direct targets of photodamage, have also developed various acclimation processes such as thermal energy dissipation through nonphotochemical quenching (NPQ), photorepair of Photosystem II (PSII), and transcriptional regulation of photosynthetic proteins. Fluctuating light is another mild but persistent type of light stress in nature, which unfortunately has been poorly investigated. Current studies, however, suggest that state transitions and cyclic electron transport are the main adaptive mechanisms for mediating fluctuating light stress in plants. Here, we review the current breadth of knowledge regarding physiological and biochemical responses to both high light stress and fluctuating light stress.